Ag–NHC Complexes in the π-Activation of Alkynes - Shiyi Yang; Tongliang Zhou; Xiang Yu; Michal Szostak (Molecules, 2023)
Silver–NHC (NHC = N-heterocyclic carbene) complexes play a special role in the field of transition-metal complexes due to (1) their prominent biological activity, and (2) their critical role as transfer reagents for the synthesis of metal-NHC complexes by transmetalation. However, the application of silver–NHCs in catalysis is underdeveloped, particularly when compared to their group 11 counterparts, gold–NHCs (Au–NHC) and copper–NHCs (Cu–NHC). In this Special Issue on Featured Reviews in Organometallic Chemistry, we present a comprehensive overview of the application of silver–NHC complexes in the p-activation of alkynes. The functionalization of alkynes is one of the most important processes in chemistry, and it is at the bedrock of organic synthesis. Recent studies show the significant promise of silver–NHC complexes as unique and highly selective catalysts in this class of reactions. The review covers p-activation reactions catalyzed by Ag–NHCs since 2005 (the first example of p-activation in catalysis by Ag–NHCs) through December 2022. The review focuses on the structure of NHC ligands and p-functionalization methods, covering the following broadly defined topics: (1) intramolecular cyclizations; (2) CO2 fixation; and (3) hydrofunctionalization reactions. By discussing the role of Ag–NHC complexes in the p-functionalization of alkynes, the reader is provided with an overview of this important area of research and the role of Ag–NHCs to promote reactions that are beyond other group 11 metal–NHC complexes.